Examining the Impact of Bank Credits on the International Marketing Enhancement Capability of Small and Medium-Sized Enterprises - Javad Tahmasebi, Mohammad (Business, Marketing, and Finance Open, 2025)
The present study aims to examine the impact of bank credits on the international marketing enhancement capability of small and medium-sized enterprises (SMEs). This study is applied in terms of purpose and descriptive-correlational in terms of methodology. The statistical population of this research includes managers, experts, and accountants of SMEs in Tehran. The sampling method is random, and the sample size is estimated to be approximately 140 individuals using Cochran’s formula. Research data were collected through a questionnaire. Cronbach’s alpha and composite reliability were used to assess the reliability of the instrument. To evaluate the validity of the instrument, content validity was confirmed through expert opinions. The structural equation modeling (SEM) method was employed to test the research hypotheses using SmartPLS2 statistical software. The research findings indicate that bank credits influence the capability of planning enhancement in international marketing for SMEs. Furthermore, bank credits impact the capability of information and communication management enhancement in international marketing for SMEs. Additionally, bank credits affect the capability of product development and pricing in international marketing for SMEs.